Fabrication of an experimental setup to study the flow of convergent-divergent nozzle (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
Nozzle is a flow passage of varying cross sectional area. It is the most important and basic piece of engineeringhardware associatedwithpropulsionand the highspeed flowof gases. Thisisintended to visualize the flow through this type of nozzle at a range of conditions. The usual configuration for a converging diverging (CD) nozzle is shown. Gas flows through the nozzle from a region of high pressure (usually referred to asthe chamber) to one of low pressure (referred to as the ambient). The chamber is usually big enough so that any flowvelocities here are negligible. The pressure here is denoted by the symbol P. Gas flows from the chamber into the converging portion of the nozzle, past the throat, through the diverging portion and then exhausts into the ambient as a jet. The ambient pressure at different cross sectional position of the nozzle is referred asthe ‘back pressure’ and given the symbol Pb . An experimental setup is designed to measure the Pb for a fixed value of P and a plot between the axial length versus pressure ratio is plotted which shows the flow behaviour at different chamber pressures. The axial lengthistakenfrom the nozzle throat.Bourdonpressure gauges are used to measure the pressure the bourdon gauges are stationary and the nozzle is moving axially with the help of rotating spindle attached to it.
Keywords: Cylindrical flowpassage; Back pressure